Luis Enrique Cam, El corresponsal del Huáscar. Crónicas de Julio Octavio Reyes. Lima, Mesa Redonda, 2015 - Laguerre Kleimann, Michel (Mercurio Peruano. Revista de Humanidades, 2020)
Luis Enrique Cam, El corresponsal del Huáscar. Crónicas de Julio Octavio Reyes. Lima, Mesa Redonda, 2015.